The Development of Behavioral Assessment Support System Website in AISEC - Hartina, Febriana Tri; Hakim, Abdul Barir (I-STATEMENT, 2018)
Current technological developments indirectly have an impact on the development of the database and internet industries. The ease that is always provided bytechnology in helping the daily lives of users makes market demand bigger. A website is a collection of related web pages, including multimedia content, usually identified with a common domain name, and published on at least one web server that provides an open platform for developers to build websites on various devices.This also affects organizations such as AIESEC, the difficulty of its members in completing many and complicated Behavioral Assessment makes its members not do mandatory things in the organization. This study aims to build a website that helps AIESEC members conduct behavioral assessments. The research used SDLC (Software Development Life Cycle) approach with the Waterfall model. This Behavioral Assessment Support System website was built using MySQL. The programming language used is PHP. The framework used is Laravel. The result of this study is the development of a prototype website-based BehavioralAssessment Support System.